Reduced brain activation during inhibitory control in children with COMT Val/Val genotype - Cope, Lora M. (Brain Behav, 2016)
INTRODUCTION: Behavioral undercontrol is a well‐established risk factor for substance use disorder, identifiable at an early age well before the onset of substance use. However, the biological mechanistic structure underlying the behavioral undercontrol/substance use relationship is not well understood. The enzyme catechol O‐methyltransferase (COMT) catabolizes dopamine and norepinephrine in the prefrontal cortex and striatum, brain regions involved in behavioral control. The goal of this work was to investigate the association between genetic variation in COMT functioning and fronto‐striatal brain functioning during successful inhibitory control, a critical aspect of behavioral control. METHODS: Participants were 65 (22 female) 7–12 year olds who were genotyped for the functional COMT Val(158)Met (rs4680) single‐nucleotide polymorphism and underwent functional magnetic resonance imaging while performing a go/no‐go task. The majority of the sample (80%) had at least one parent with a history of alcohol use disorder and were thus at heightened risk for substance use disorders. RESULTS: There was a significant main effect of genotype on brain activation in left and right putamen during successful versus failed inhibition and in right inferior frontal gyrus/insula during successful inhibition versus baseline. Follow‐up tests revealed that Met homozygotes had greater activation in each region relative to Val homozygotes. CONCLUSIONS: These results are relevant for understanding how specific genes influence brain functioning related to underlying risk factors for substance use disorders and other disinhibitory psychopathologies.